Analysis of General Secondary Exam Questions in Jordan for the subject of Jordan History in light of the levels of knowledge field according to Bloom’s Classification – An analytical study for the subject of Jordan’s history – - Al- Shouqairat, Ghazzi Abdullah (Journal of Educational and Psychological Sciences, 2020)
The study aimed to analyze the questions of high school exams in Jordan for the subject of the history of Jordan in the light of the levels of knowledge field according to Bloom’s classification; To find out the suitability of the questions of high school exams for the goals for which they were set. The study population and its sample consisted of the high school exam questions for the history of Jordan for the academic years 2017- 2019, the sample of the study was chosen by intentional method, the researcher used the descriptive analytical method to conduct the study, and the study tool was represented in the card analysis of levels of cognitive field according to Bloom’s classification. Content or content and the stability of the tool (87.4%). Statistical treatment was used by extracting iterations and percentages, As the percentage of questions related to the level of recall (52, 5%) and the percentage of questions related to the level of understanding (41, 4%), There was a marked decrease in the questions of application and analysis, As the percentage of questions related to the level of application reached (2.20%) and the percentage of questions related to the level of analysis (3.9%) and the questions of synthesis and evaluation were completely absent. And by (0%), The researcher recommended focusing on the questions that measure the higher levels of knowledge, and holding training courses for teachers and supervisors of the history of Jordan and the holding of courses and workshops for the authors of the questions of high school exams for the history of Jordan, So that they fit the cognitive levels.